THE ROLE OF GOVERNMENT IN PROMOTING HANDICRAFT INDUSTRY: A CASE STUDY OF KASHMIR - Majeed, Ishfaq; Bhat, Akhter Hussain; Azam, Rayees (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In India, the handicraft industry is the second largest rural employment industry after agriculture. Handicrafts are typically produced in the unorganised industry. There was an underestimation of the potential of the handicraft industry, which can play a significant part in the economy. Artisans face low wages, job inconsistencies, a lack of technological expertise, and a lack of new design. Several government and non-governmental programmes are also in operation, but they are either ineffective or do not impact the majority of artisans. In the present study the researchers focuses on the present trends of different handicraft schemes implemented under the 12th five-year plan. The study also explores the ground reality of the existing government’s programmes in Jammu and Kashmir towards promoting handicraft industry. The present research will help policymakers create appropriate initiatives to expand the handicraft industry and artisans, as well as change existing plans.